Homoseksualiteit en fascisme : scholingsmap. - Vermeulen, Mary; Odijk, Michiel; Verschuren, Peter; Schuyf, Judith; Oosterhuis, Harry; Koenders, Pieter (Utrecht : AFKU COC, 1984)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie